A , B and C take turns rolling a fair die (with equal probability of it showing any of { 1 , 2 , 3 , 4 , 5 , 6 } , and the as soon as one of them gets a six, the game ends and he wins.
A gets the first chance to roll the die ,followed by B , and then C , followed by A again if none of them gets a six.
Let the probability of A winning the game be b a , that of B be d c and that of C winning the game be f e , with a , b , c , d , e , f being positive integers, with g cd ( a , b ) = g cd ( c , d ) = g cd ( e , f ) = 1 .
Find a + b + c + d + e + f .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If Player X wins we write X , else we write X ′ .
Also we note that the probability of getting a 6 is 6 1 while that of getting any of the other 5 numbers is 6 5 .
So A wins if any of the following events happen,
A , A ′ B ′ C ′ A , A ′ B ′ C ′ A ′ B ′ C ′ A , A ′ B ′ C ′ A ′ B ′ C ′ A ′ B ′ C ′ A , . . .
Thus the total probability of A winning is 6 1 + 6 . 6 . 6 . 6 5 . 5 . 5 . 1 + 6 . 6 . 6 . 6 . 6 . 6 . 6 5 . 5 . 5 . 5 . 5 . 5 . 1 + . . . = 6 1 + ( 6 5 ) 3 6 1 + ( ( 6 5 ) 3 ) 2 6 1 + . . . = 1 − ( 6 5 ) 3 6 1 = 9 1 3 6 (by the formula for the sum of an infinite geometric progression)
Similarly B wins if any of the following events happen,
A ′ B , A ′ B ′ C ′ A ′ B , A ′ B ′ C ′ A ′ B ′ C ′ A ′ B , A ′ B ′ C ′ A ′ B ′ C ′ A ′ B ′ C ′ A ′ B , . . .
and the total probability of B winning the game will come out to be 9 1 3 0 .
Similarly the total probability of C winning the game turns out to be 9 1 2 5 .
So we get 3 6 + 9 1 + 3 0 + 9 1 + 2 5 + 9 1 = 3 6 4
The first three rolls give 6 3 possible outcomes.
In the 5 3 cases where there is no six, nobody wins. However, the probabilities in a second (third, fourth, ...) round are the same as in the first round. Therefore we only need to consider the 6 3 − 5 3 cases in which there is actually a winner.
The probabilities are of the form P ( i ) = 6 3 − 5 3 5 i − 1 ⋅ 6 3 − i . The numerator and denominator are coprime. If we add them all together, we get ∑ ( numerators + denominators ) = ( 6 3 − 5 3 ) + 3 ⋅ ( 6 3 − 5 3 ) = 4 ⋅ ( 6 3 − 5 3 ) = 3 6 4 .
Generalization: With n players and a die that has k possible outcomes, the probabilities will be P ( i ) = k n − ( k − 1 ) n ( k − 1 ) i − 1 ⋅ k n − i , i = 1 , … , n with coprime numerators and denominators; adding them all gives a total of ( n + 1 ) ( k n − ( k − 1 ) n ) .
Hack:
The sample space is not 6 3 = 2 1 6 . If all three throw non-sixes, the turn passes back to A, and we're effectively in an identical situation as the start. Thus the sample space is only when some of them throw a six in the first throw, which is 6 3 − 5 3 = 9 1 . Thus we know that P ( A ) , P ( B ) , P ( C ) have denominator 91 before simplifying. Additionally, they add up to 1, so their numerators sum up to 91. Adding all of them together, this gives 364; since there is no smaller number in the choices, this must be the answer.
I don't think this is a hack at all, because after all you did not cheat in anyway in getting the sum, and you obtained it in a perfectly logical way, so I think it's a Brilliant way, though I had never thought of such a way. I love this.
P ( A ) = 6 1 + 6 5 × 6 5 × 6 5 P ( A ) ⇒ P ( A ) = 9 1 3 6
P ( B ) = 6 5 × 6 1 + 6 5 × 6 5 × 6 5 P ( B ) ⇒ P ( B ) = 9 1 3 0
P ( C ) = 6 5 × 6 5 × 6 1 + 6 5 × 6 5 × 6 5 P ( C ) ⇒ P ( C ) = 9 1 2 5
Problem Loading...
Note Loading...
Set Loading...
Let P ( X ) be the probability that player X wins.
We can think in this way:
'If A got a non-six, start a new game in which B rolls first, then C , then A .'
So P ( B ) = 6 5 P ( A )
Similarly, P ( C ) = 6 5 P ( B )
After some calculations of ratios,
b a = 9 1 3 6 , d c = 9 1 3 0 , f e = 9 1 2 5
Answer = 3 6 + 9 1 + 3 0 + 9 1 + 2 5 + 9 1 = 3 6 4